Approaching the Dizzy Patient (An Overview) - Ghunaim, Mohammad (Jordan Medical Journal, 2020)
Dizziness is known to be one of the most burdensome medical complaints, which is frequently encountered by physicians all over the globe. Despite many advances in laboratory and radiologic investigations, in addition to the advents in vestibular testing technologies, deep knowledge of the basic concepts remains the cornerstone in understanding balance.We, therefore, aimed to impart a systematic way for approaching the dizzy patient, and provide the reader with review of the paramount steps for dealing with dizziness cases, through overviewing the basic concepts, understanding the definition of different dizziness sensations, detailed history taking and physical examination, investigations and performing classical maneuvers for balance and vestibular system targeted by history and physical examination.Using the above mentioned approach will allow the physician to diagnose and manage most of the common pathologies, without performing unneeded laboratory tests, radiologic imaging or vestibular tests.